2019
DOI: 10.1016/j.epidem.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Superensemble forecast of respiratory syncytial virus outbreaks at national, regional, and state levels in the United States

Abstract: Respiratory syncytial virus (RSV) infections peak during the winter months in the United States, yet the timing, intensity, and onset of these outbreaks vary each year. An RSV vaccine is on the cusp of being released; precise models and accurate forecasts of RSV epidemics may prove vital for planning where and when the vaccine should be deployed. Accurate forecasts with sufficient spatial and temporal resolution could also be used to support the prevention or treatment of RSV infections. Previously, we develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Although the ensemble performed well, there are many avenues for further improvement. The ensemble forecast weighted the models equally, but weighting based on historical performance may improve forecast skill (McAndrew and Reich 2019; Reich, McGowan, et al 2019; Viboud et al 2018; E. L. Ray and Reich 2018; Yamana, Kandula, and Shaman 2016; Reis et al 2019; Brooks et al 2018). However, any weighting method will need to be dynamic and allow for the incorporation of new models, potential changes in existing models, and the different sets of locations forecasted by each model.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ensemble performed well, there are many avenues for further improvement. The ensemble forecast weighted the models equally, but weighting based on historical performance may improve forecast skill (McAndrew and Reich 2019; Reich, McGowan, et al 2019; Viboud et al 2018; E. L. Ray and Reich 2018; Yamana, Kandula, and Shaman 2016; Reis et al 2019; Brooks et al 2018). However, any weighting method will need to be dynamic and allow for the incorporation of new models, potential changes in existing models, and the different sets of locations forecasted by each model.…”
Section: Discussionmentioning
confidence: 99%
“…During an Ebola outbreak, real-time forecasting has the potential to support decision-making and allocation of resources, but highly accurate forecasts have proven difficult for Ebola [8,9] as well as other diseases [10][11][12][13]. Highly accurate forecasts of small, noisy outbreaks may be a fundamentally elusive ideal [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has found that probabilistic forecasts can have relatively high accuracy within a few weeks, though they become less useful as time horizons grow longer 8 , and short-term forecasts may provide useful information for response organizations. 3 In this paper we apply a suite of independent methods of real-time forecasting to the Eastern DRC outbreak, to generate both short-term and long-term projections of future case counts as of the time of writing. We validate short-term projections by scoring projections derived from case count reports obtained earlier in the outbreak against subsequent known counts.…”
mentioning
confidence: 99%